2014
DOI: 10.3944/aott.2014.3181
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of Oxford Phase 3 unicompartmental knee arthroplasty in obese patients

Abstract: Oxford Phase 3 UKA with mobile bearing has good mid-term results in obese patients over 60 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
12
1
1
Order By: Relevance
“…They found no complications during this time period except three insert dislocations. [12] The reported results of these studies are consistent with the early-and mid-term results reported by the Oxford designer surgeons. On the other hand, our findings are consistent with the studies using the registry data of England, Sweden, and Finland, suggesting that long-term follow-up studies with larger sample sizes are more reliable.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…They found no complications during this time period except three insert dislocations. [12] The reported results of these studies are consistent with the early-and mid-term results reported by the Oxford designer surgeons. On the other hand, our findings are consistent with the studies using the registry data of England, Sweden, and Finland, suggesting that long-term follow-up studies with larger sample sizes are more reliable.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies on Oxford UKA have also been conducted in Turkey, reporting successful short-and mid-term clinical results. [10][11][12] For example, Aslan et al, [10] conducted a 28-month follow-up study on cemented Oxford UKA in 27 patients in 2007 and reported that only two (7.4%) patients required revision surgery due to tibial collapse. Furthermore, in 2010, Parmaksızoğlu et al [11] reported the outcomes of 38 cases of cemented Oxford UKA for 24-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In einer Studie von Murray et al anhand von 2438 Patienten nach medialen OUKR konnte kein Zusammenhang im klinischen funktionellen Outcome oder der Versagerrate mit dem Body-Mass-Index festgestellt werden [44]. Ähnliche Ergebnisse konnten in weiteren Studien bestätigt werden [43,45,46]. Ebenso konnte anhand ausgebauter Polyäthylen-Inlays kein Einfluss auf die lineare Abriebrate des Polyäthylens durch Übergewicht festgestellt werden [6], weshalb eine Gewichtsgrenze in den Selektionskriterien für die Oxford-Schlittenprothese nicht enthalten ist [16,44].…”
Section: Gewichtunclassified